Pengaruh Ketepatan Waktu Visite Dokter terhadap Kepuasan Pasien Rawat Inap Peserta BPJS Kesehatan: Sebuah Tinjauan Pustaka - Situmorang, Cindy (Fakultas Kedokteran Universitas Lampung, 2025)
Patient satisfaction is a crucial indicator of service quality within Indonesia's National Health Insurance system. For inpatients in the BPJS Kesehatan Class 3 category, a vulnerable population segment, the timeliness of doctor's rounds is a significant factor influencing their experience; thus, this article aims to critically analyze its effect. Employing a narrative literature review methodology, empirical evidence from relevant studies was synthesized and critically analyzed to construct a comprehensive conceptual model. The analysis reveals a positive and statistically significant relationship between the timeliness of doctor's rounds and patient satisfaction. Furthermore, timeliness functions as a